The integrated inventory management with forecast system - Noor Ajian Mohd Lair; Ng, Chin‐Chong; Abdullah Mohd. Tahir; Rachel Fran Mansa; Teo, Kenneth Tze Kin (DEStech Publications, 2014)
Inventory Management System is very important for driving a company into better achievement. The main objective of inventory management is to keep the inventory level as low as possible and meet customers’ demand. This project centers on development of the computerized integrated inventory management and forecast system for the Guan Lee Sdn Bhd. In this project, the exponential smoothing is selected to predict demands as inputs to control the computerised inventory management system. The integrated system was written using the Visual Basic 2008. This integrated inventory management and forecast system has the ability to forecast while effectively control on inventory level with six specific features of alert, creation, inventory, transfer, search and reports. Performance of the system was analyzed with three types of forecast value (actual and adjusted forecast values). From the results, the actual forecast values tend to move toward the ideal one. Thus, the forecast system is proved to be reliable and accurate. The suggested improvements are auto recording of historical data, attachment of picture to each item, and sending notification through text message.